2022
DOI: 10.3389/fchem.2022.1023542
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic silver nanoparticles as antifungal agents

Abstract: In recent years, an increase in multidrug-resistant fungal strains has been observed, which, together with the limited number of clinically available antifungal agents, highlights the need for the development of new antifungal agents. Due to the proven antifungal activity of silver nanoparticles (AgNPs), there is a growing interest in their use in the treatment of fungal infections. Nanoparticles are usually synthesised through a variety of physical and chemical processes that are costly and pollute the enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 84 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Electrostatic attraction between AgNPs and surface of fungi results in the attachment of NPs to the surface of fungal cells with a further membrane damage and penetration of biogenic AgNPs inside the cells and induction of intracellular ROS. The overgeneration of ROS damages the intracellular organelles and triggers cell death [ 49 ]. Moreover, the silver cations can be released from AgNPs owing to the large surface area to volume ratio of AgNPs and these ions can bind to the enzyme protein sulfhydryl (–SH) and DNA bases and alter their functions [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Electrostatic attraction between AgNPs and surface of fungi results in the attachment of NPs to the surface of fungal cells with a further membrane damage and penetration of biogenic AgNPs inside the cells and induction of intracellular ROS. The overgeneration of ROS damages the intracellular organelles and triggers cell death [ 49 ]. Moreover, the silver cations can be released from AgNPs owing to the large surface area to volume ratio of AgNPs and these ions can bind to the enzyme protein sulfhydryl (–SH) and DNA bases and alter their functions [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Balavijayalakshmi and Ramalakshmi reported the effectiveness of the silver nanoparticles synthesized from Carica papaya peel against Escherichia coli and Staphylococcus aureus [14]. Mussin and Giusiano [28] further suggested that biogenic AgNPs perform much better as fungicidal agents when they are combined with antifungal drugs. Saxena and Ayushi [29] have reported the fungicidal characteristics of AgNPs synthesized even from the plant pathogenic fugal strain S. sclerotiorum MTCC 8785 against the T. harzianum strain.…”
Section: Discussionmentioning
confidence: 99%
“…No cell receptors or membrane channels for the absorption of silver have been identified to yet. However, it has been discovered that Ag + is imported through the high-affinity copper transporter (Ctr1) [ 40 ].…”
Section: Mechanism Of Action Against Fungusmentioning
confidence: 99%
“…Nanoparticles have been prepared and modified using natural substances derived from bacteria, fungus, and plants [ 46 ]. For instance, sildenafil citrate, geniposidic acid, 3,5-dimethylphenol, Action mechanism of AgNPs against fungi [ 40 ]. palmitic acid, borneol, 2-hexyl-1-octanol, and -terpinyl acetate were used as phytochemicals in an aqueous leaf extract from Acalypha indica that was used to synthesize spherical AuNPs with a 20 nm size shown in Figure 7(b) [45].…”
Section: Mechanism Of Action Against Bacteriamentioning
confidence: 99%